Calanthe anthropophora Ridley-a Rare Orchid and a New Find for India from Meghalaya - Goswami, N.; Joseph, J. (Indian Forester, 1985)
A detailed illustrated description of Calanthe anthropophora Ridley-an addition to the flora of India in Meghalaya bas been given. It is known previously only from Thailand.